2000
DOI: 10.1176/ps.51.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Behavior of Louisiana Students in Grades 6 Through 12

Abstract: A significant minority of Louisiana students in grades 6 through 12-15.9 percent--acknowledged gambling-related symptoms and life problems. The association of problem and pathological gambling with use of alcohol, tobacco, and marijuana provides preliminary support for the inclusion of gambling among other adolescent risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 9 publications
2
40
1
6
Order By: Relevance
“…A meta-analysis on published and unpublished studies on problem gambling prevalence rates in the USA and Canada from 1985 to 1994 suggested that between 4.4% and 7.4% of adolescents exhibit severe gambling problems (Shaffer & Hall, 1996). These figures have been confirmed in more recent research in both the USA and Canada (e.g., Derevensky & Gupta, 2000;Gupta & Derevensky, 1998;Westphal et al, 2000;Wiebe, Cox, & Mehmel, 2000), although lower figures have also been reported (e.g., Ladouceur et al, 1999;Poulin, 2000;Volberg, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…A meta-analysis on published and unpublished studies on problem gambling prevalence rates in the USA and Canada from 1985 to 1994 suggested that between 4.4% and 7.4% of adolescents exhibit severe gambling problems (Shaffer & Hall, 1996). These figures have been confirmed in more recent research in both the USA and Canada (e.g., Derevensky & Gupta, 2000;Gupta & Derevensky, 1998;Westphal et al, 2000;Wiebe, Cox, & Mehmel, 2000), although lower figures have also been reported (e.g., Ladouceur et al, 1999;Poulin, 2000;Volberg, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…The popular press has frequently reported alarming incidents involving young gamblers. Numerous surveys of U.S. states have indicated high rates of youth problem gambling (e.g., Shaffer et al 1997;Westphal et al 2000). Research has shown that adolescent onset of gambling is associated with greater gambling involvement in adulthood (Burge et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a Louisiana survey of students in grades 6 through 12, Westphal et al (2000) found that problem gambling was more prevalent among males than females, more prevalent among minority group members than whites. In a high school survey conducted in Alabama, Mississippi and Oregon, Langhinrichsen et al (2004) had those same findings.…”
Section: Introductionmentioning
confidence: 99%
“…La relación encontrada en este estudio de 2,5:1 (hombremujer), se acerca a lo reportado por investigadores en diferentes culturas (Adlaf y Ialomiteanu, 2000;Ko, Yen, Chen, Chen y Yen, 2005;Westphal, Rush, Stevens y Johnson, 2000). Pietrzack, Ladd y Petry (2003), señalan al sexo masculino como factor de riesgo para el juego patológico y otros estudios, entre ellos el de Huang y Boyer (2007), han encontrado una razón de 3:1.…”
Section: Discussionunclassified